Misfolding of fukutin-related protein (FKRP) variants in congenital and limb girdle muscular dystrophies - Esapa, Christopher T.; McIlhinney, R. A. Jeffrey; Waite, Adrian J.; Benson, Matthew A.; Mirzayan, Jasmin; Piko, Henriett; Herczegfalvi, Ágnes; Horvath, Rita; Karcagi, Veronika; Walter, Maggie C.; Lochmüller, Hanns; Rizkallah, Pierre J.; et al. (Frontiers in Molecular Biosciences, 2023)
Fukutin-related protein (FKRP, MIM ID 606596) variants cause a range of muscular dystrophies associated with hypo-glycosylation of the matrix receptor, -dystroglycan. These disorders are almost exclusively caused by homozygous or compound heterozygous missense variants in the FKRP gene that encodes a ribitol phosphotransferase. To understand how seemingly diverse FKRP missense mutations may contribute to disease, we examined the synthesis, intracellular dynamics, and structural consequences of a panel of missense mutations that encompass the disease spectrum. Under non-reducing electrophoresis conditions, wild type FKRP appears to be monomeric whereas disease-causing FKRP mutants migrate as high molecular weight, disulfide-bonded aggregates. These results were recapitulated using cysteine-scanning mutagenesis suggesting that abnormal disulfide bonding may perturb FKRP folding. Using fluorescence recovery after photobleaching, we found that the intracellular mobility of most FKRP mutants in ATP-depleted cells is dramatically reduced but can, in most cases, be rescued with reducing agents. Mass spectrometry showed that wild type and mutant FKRP differentially associate with several endoplasmic reticulum (ER)-resident chaperones. Finally, structural modelling revealed that disease associated FKRP missense variants affected the local environment of the protein in small but significant ways. These data demonstrate that protein misfolding contributes to the molecular pathophysiology of FKRP-deficient muscular dystrophies and suggest that molecules that rescue this folding defect could be used to treat these disorders.